Major interventions for sustainable wetland resource management - Khan, M. Saiful Islam; Irfanullah, Haseeb Md.; Nishat, Ainun; IUCN--The World Conservation Union. Bangladesh Country Office (Dhaka : IUCN--The World Conservation Union, Bangladesh Country Office, 2005)
With reference to Bangladesh.
Includes bibliographical references (pages 132-134).
ARC
Keywords: Wetlands -- Bangladesh; Wetlands -- Bangladesh -- Management